Growth in a circular economy - Marco Compagnoni; Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2021)
We present a model of natural resources and growth that stresses the influence of an incomplete circularity of exhaustible natural resources. In particular, we analyze the recycling process and the material balance principle, two fundamental aspects of a circular economy. When market failures arise or complete recycling is not possible for technical reasons, then the equilibrium outcomes in terms of output, consumption, and prices for the material inputs are distorted compared to the socially optimal solution. However, the introduction of a market for waste and a system of subsidies/taxes on virgin and recycled resources enables an internalization of the externalities. The importance of technological progress in order to foster "circularity", i.e. both to improve resource efficiency in the production process and to enhance the backflow of materials from waste to production, is highlighted.
urn:nbn:de:bsz:21-dspace-1151204; hdl:10900/115120
Keywords: O41; Q01; Q32; Q53; 330; Circular economy; economic growth; natural resources; recycling